1986
DOI: 10.3109/10641968609046570
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Stable High Blood Pressure in Adolescents

Abstract: We studied the relative importance of the initial BP and associated factors in adolescents to predict stable high BP. Out of 17,634 children aged 12-13 yrs an upper group/the upper 5% of the distribution curves for both SBP and DBP/a lower group/10% random from the remainder/were yearly followed for 4 yrs/boys: 1680, girls: 1643/. About 2/3 of children remained at the same percentile point: less than 30% and greater than or equal to 70% of SBP and half of them of DBP distribution. Significant positive tracking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Although the association between mild hyperuricemia and hypertension has previously been described in several studiesbothinadultsandinchildren, 1,3,4,6,26 a relationship between UA and prehypertension has mainly been reported in adults, 27 with only a few, relatively small studies carried out in children with white coat and borderline hypertension. 4,5,16 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the association between mild hyperuricemia and hypertension has previously been described in several studiesbothinadultsandinchildren, 1,3,4,6,26 a relationship between UA and prehypertension has mainly been reported in adults, 27 with only a few, relatively small studies carried out in children with white coat and borderline hypertension. 4,5,16 …”
Section: Discussionmentioning
confidence: 99%
“…To fully account for age, gender, and height, according to the tables published in the fourth report on the diagnosis, evaluation, and treatment in children and adolescents, 23 we used BP z-scores rather than raw BP values, which makes our observations more reliable as compared with those of a variety of previous reports. 1,2,4,6,16 Furthermore, to the best of our knowledge, for the first time several clinical and biohumoral variables have been concurrently collected and analyzed in a group of referred children.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…15 This rigorous methodological approach makes our observations more reliable as compared with those of a variety of previous reports. 1,6,26,28 Moreover, our study represents one of the few evidences reported in the literature of the effectiveness of an educational program of lifestyle changes in a large cohort of children in a real life context. 20 Finally, there are some limitations to our study.…”
Section: Discussionmentioning
confidence: 99%
“…In Hungary 25-30% of the adult population is hypertensive. Earlier Környei et al [34,35] and Török et al [36] performed blood pressure screening in a population of children under the age of 14 years, whereas Pá ll et al [37] undertook such measurements in subjects aged between 14 and 18 years in a Hungarian city.…”
Section: Discussionmentioning
confidence: 99%